Analisis Hubungan Antara Tingkat Penggunaan Media Digital Dengan Pola Belajar Mahasiswa: Suatu Kajian Meta-Analisis - Dian Maharani Buulolo; Talabu Tumimman Kevin Keasada Buulolo (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
This meta-analysis examines the relationship between digital media usage and student learning patterns in higher education. Through a systematic review of 47 studies published between 2014-2024, encompassing 28,465 students across 23 countries, we analyzed the multifaceted impact of digital media consumption on academic learning behaviors. The study employed a random-effects model and moderator analysis to investigate various aspects of digital media usage, including social media, educational platforms, and entertainment consumption. Results indicate a significant correlation (r = 0.42, p < 0.001) between digital media usage patterns and changes in student learning behaviors, with notable variations across different types of digital media and academic disciplines. The findings suggest that while moderate digital media usage can enhance learning engagement, excessive consumption may lead to decreased academic performance and altered study patterns. This meta-analysis provides crucial insights for educational institutions and policymakers in developing digital media integration strategies for higher education.